Identifikasi Kesulitan Belajar Mahasiswa Program Studi Ensino De Física Universitas Nasional Timor Lorosae Angkatan 2023 - Maria Lia Felizarda Freitas; Fernão dos Santos Rodrigues (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
Learning difficulties are disorders experienced by students due to various obstacles such as intellectual abilities, demands of academic institutions, family economic conditions, and employment that result in low learning outcomes. This study aims to identify the factors that cause learning difficulties for students of batch 2023 in the Ensino de Física Study Programme at the National University of East Timor, especially in the General Physics and Eksperiment 1 courses. This study used a mixed qualitative and quantitative approach. Data were collected through an open-ended questionnaire filled out by 50 students as a sample. The results showed that the study programme placement factor was one of the main causes of learning difficulties. Many students were placed in study programmes that were not their choice, resulting in low interest in learning. In addition, students' mathematical intellectual abilities also play a significant role, where most students do not master basic mathematics such as multiplication, division, and differential. This causes them difficulty in solving physics problems mathematically and in conducting Eksperiments to test concepts, laws and formulas that have been learnt. Students' learning difficulties are influenced by external factors such as the mismatch of study programme placement with students' choices, and internal factors such as intellectual abilities in basic mathematics and physics. Nevertheless, most students showed interest in attending the class, which can help overcome learning difficulties and have a positive impact on end-of-semester learning outcomes.